The development and evaluation of modularized teacher's packages on techniques of using drosophila in high school biology - Samonte, Carolina Bautista (1978)
This study attempted to find out what specific topic of modularized instructional materials should be constructed for techniques in genetics for in-service training of biology teachers. The methodology involved three phases: 1. modification of some techniques in culturing, handling the Drosophila, and preparing the salivary gland chromosome; 2. specification of the objectives and problems; and 3. field testing of the modules to 20 highschool biology teachers of Ilocos Norte. Results of the data gathered provide information on the effectiveness and workability of the modules.
Vita.
Thesis (M.A. Biology Education)--University of the Philippines, Diliman.
Keywords: Biology -- Study and teaching (Secondary) -- Activity programs -- Philippines -- Ilocos Norte; Biology teachers -- Training of -- Philippines -- Ilocos Norte; Drosophila; Academic achievement -- Philippines -- Ilocos Norte; High school students -- Philippines -- Ilocos Norte; Teaching -- Philippines -- Ilocos Norte -- Aids and devices